Skin Pathology Induced by Snake Venom Metalloproteinase: Acute Damage, Revascularization, and Re-epithelization in a Mouse Ear Model - Jiménez Álvarez, Natalia (2008)
Viperid snakebite envenomation induces blistering and dermonecrosis. The pathological alterations induced by a snake venom metalloproteinase in the skin were investigated in a mouse ear model. Metalloproteinase BaP1, from Bothrops asper, induced rapid edema, hemorrhage, and blistering; the latter two effects were abrogated by preincubation with the metalloproteinase inhibitor batimastat. Neutrophils did not play a role in the pathology, as depletion of these cells resulted in a similar histological picture. Blisters are likely to result from the direct proteolytic activity of BaP1 of proteins at the dermal-epidermal junction, probably at the lamina lucida, as revealed by immunostaining for type IV collagen and laminin. Widespread apoptosis of keratinocytes was detected by the TUNEL assay, whereas no apoptosis of capillary endothelial cells was observed. BaP1 induced a drastic reduction in the microvessel density, revealed by immunostaining for the endothelial marker vascular endothelial growth factor receptor-2. This was followed by a rapid angiogenic response, leading to a partial revascularization. Skin damage was followed by inflammation and granulation tissue formation. Then, a successful re-epithelization process occurred, and the skin of the ear regained its normal structure by 2 weeks. Venom metalloproteinase-induced skin damage reproduces the pathological changes described in snakebitten patients.